Identification and Risk Management Efforts In Supply Chain Activities Using The House Of Risk Method In Sempe Arimanis Small and Medium Enterprises - Dindi Asparilla Putri Sutanto; Yasrin Zabidi; Suhanto Suhanto; Riani Nurdin; Eko Poerwanto; Prasidananto Nur Santoso (Institut Teknologi Dirgantara Adisutjipto, 2026)
Sempe Arumanis, a small and medium enterprise (SME), operating in Yogyakarta and producing Sempe Arumanis, faces supply chain risks such as inaccurate orders, late supplies, and damaged raw materials. Therefore, risk management is needed to identify and mitigate the risks present in the SME. Therefore, risk identification is necessary to minimize these risks. The House of Risk (HOR) method is used to identify risks and take preventive measures. The results of the analysis revealed three high-frequency risks faced by Sempe Arumanis small and medium enterprises: a lack of historical data or accurate information, dependence on a single supplier, and restrictions on raw material purchases that disrupt operations and customer satisfaction. Risk management measures include seeking more than one supplier, routinely checking stock, labeling shelves, negotiating contracts and inventory, conducting quality checks before shipment, training in quality control, communicating between sales and warehouse teams, and implementing an integrated system.